Similarities and divergences in the metabolism of immune cells in cancer and helminthic infections - Esperante, Diego; Gutiérrez, Mónica Itzel Martínez; Issa, Mark E.; Schcolnik-Cabrera, Alejandro; Mendlovic, Fela (Frontiers in Oncology, 2023)
Energetic and nutritional requirements play a crucial role in shaping the immune cells that infiltrate tumor and parasite infection sites. The dynamic interaction between immune cells and the microenvironment, whether in the context of tumor or helminth infection, is essential for understanding the mechanisms of immunological polarization and developing strategies to manipulate them in order to promote a functional and efficient immune response that could aid in the treatment of these conditions. In this review, we present an overview of the immune response triggered during tumorigenesis and establishment of helminth infections, highlighting the transition to chronicity in both cases. We discuss the energetic demands of immune cells under normal conditions and in the presence of tumors and helminths. Additionally, we compare the metabolic changes that occur in the tumor microenvironment and the infection site, emphasizing the alterations that are induced to redirect the immune response, thereby promoting the survival of cancer cells or helminths. This emerging discipline provides valuable insights into disease pathogenesis. We also provide examples of novel strategies to enhance immune activity by targeting metabolic pathways that shape immune phenotypes, with the aim of achieving positive outcomes in cancer and helminth infections.